Hubungan Agama dan Internet: Perusak sekaligus pelengkap Otoritas Agama - Busro Busro (Khazanah Multidisiplin, 2022)
This study contributes to the study of religion and media, especially the internet, an area of study that is becoming increasingly popular in religious studies. Its purpose is to discuss the relationship between religion and the internet and how it relates to traditional religious authority. This research applies qualitative research through literature study. This study's result is that the increasing number of religious content on the internet has both negative and positive effects. Another important finding is that the internet and religion follow the logic of discontinuity to religious authority, namely, seeing the internet as a destroyer of traditional religious authority. Besides, at the same time, the internet and religion can also follow the logic of continuity and complement. The internet is seen as an extension of and complementing and strengthening traditional religious authority.